Modulation of lateral positions of Bragg peaks via magnetic fields inside cancer patients: Toward magnetic field modulated proton therapy. Issue 10 (22nd September 2017) - Shao, Wencheng; Tang, Xiaobin; Bai, Yanling; Geng, Changran; Shu, Diyun; Gong, Chunhui; Chen, Da
Abstract : Purpose: This work investigated whether the Bragg peak (BP) positions of proton beams can be modulated to produce uniform doses and cover a tumor under the magnetic fields inside cancer patients, and whether magnetic field modulated proton therapy (MMPT) is effective in vital organ protection. Methods: The authors initially constructed an ideal water phantom comprising a central tumor surrounded by cuboid organ regions using GEANT4. Second, we designed the proton beams passing through the gap between two adjacent organ regions during beam configuration. Third, we simulated the beam transports under magnetic fields inside the phantom through GEANT4. Then, the beams were discarded, which did not stop in the tumor. Fourth, the authors modulated the intensities of the remaining beams to produce uniform tumor doses. Subsequently, the calculated MMPT doses were compared with those of traditional methods, such as single, opposing, orthogonal, and box fields. Moreover, the authors repeated the above research procedures for abdominal anatomies comprising tumors at the pancreatic tail and liver to evaluate whether MMPT is effective for the human anatomy. Results: For the water phantom, the vital organ doses were approximately 50%, 30%, 30%, and 15% for the single, opposing, orthogonal, and box fields, respectively. As the vital organ doses decreased, the organ volume receiving proton irradiations for the opposing, orthogonal, and box fields increased by two, two, and four times compared with that for the single field. The vital organ volume receiving proton irradiations were controlled to a fairly low level through MMPT, whereas the BP positions of the proton beams were properly modulated through the magnetic fields inside the phantom. The tumor was sufficiently covered by a 95% dose line, and the maximum tumor doses were smaller than 110%. For the pancreatic tumor case, the proton beams were curved and bypassed the kidney to generate uniform doses inside the tumor through MMPT. In the liver tumor case, the liver volume receiving proton irradiations was reduced by approximately 40% through MMPT compared with traditional methods. Conclusions: The BP positions can be intentionally modulated to produce uniform tumor doses under the magnetic fields inside cancer patients. In some special cases, the vital organs surrounding the tumor can almost be exempted from proton irradiations without sacrificing tumor dose coverage through MMPT. For the tumors inside parallel organs, the parallel organ volume receiving proton irradiations was largely reduced through MMPT. The results of this study can serve as beneficial implications for future proton therapy studies with reduced vital organ damage and complications.